Mordecai's dream in Esther-The Greek and Latin versions, character, and the tradition of interpretation - Thambyrajah, Jonathan A (Journal for the study of the Old Testament, 2019)
The book presently known as Esther was in antiquity identified as not only the book of Esther but also the book of Mordecai. The primacy of Esther or Mordecai in the book preserved by the Masoretic Text is ambiguous. It is, however, well known that there are additional components to the book of Esther, found in the Greek versions (LXX, Alpha Text) and the Vetus Latina. By examining Mordecai's dream and its interpretations, found in these additions to Esther, this study concludes that the different versions of the text correspond to different traditions of interpretation of the book of Esther. In particular, these different traditions differ in their perception of whether the story's protagonist is Esther or Mordecai.